2011
DOI: 10.1159/000328238
|View full text |Cite
|
Sign up to set email alerts
|

Plasma C3 and C3a Levels in Cryptogenic and Large-Vessel Disease Stroke: Associations with Outcome

Abstract: Background and Purpose: Inflammation seems to be a key player in the pathophysiology of stroke. In this study, we compared plasma C3 and C3a levels in cryptogenic and large-vessel disease (LVD) subtypes of ischemic stroke and control subjects and evaluated their association to outcome at 3 months and 2 years. Methods: C3 and C3a levels in plasma of 79 cryptogenic stroke and 73 LVD stroke patients, sampled within 10 days and at 3 months after stroke, and age- and sex-matched control subjects from the Sahlgrensk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 56 publications
5
29
0
Order By: Relevance
“…Interestingly, recent study indicated that elevated MBL levels could be considered as an independent stroke risk factor in Chinese population [46] . The elevated blood levels of C3 complement protein in IS patients have been reported earlier by us [47] , as well as by other research groups [48][49][50][51][52] . However, this is the first study demonstrated the increased hemolytic activity of C3 in the blood of IS-affected subjects.…”
Section: Discussionsupporting
confidence: 78%
“…Interestingly, recent study indicated that elevated MBL levels could be considered as an independent stroke risk factor in Chinese population [46] . The elevated blood levels of C3 complement protein in IS patients have been reported earlier by us [47] , as well as by other research groups [48][49][50][51][52] . However, this is the first study demonstrated the increased hemolytic activity of C3 in the blood of IS-affected subjects.…”
Section: Discussionsupporting
confidence: 78%
“…Both C4a and C3a levels are predictive of the responses of esophageal cancer patients to chemoradiation (Maher et al, 2011). In more obviously inflammatory disorders, C3a (and to a lesser extent C4a) have been shown to be potentially useful markers in dermatomyositis (Campo et al, 2007), aneurysmal subarachnoid hemorrhage (Mack et al, 2007), acute Lyme disease in tick-bite patients (Shoemaker et al, 2008;Stricker et al, 2009) (Fassbender et al, 2009), adverse pregnancy outcomes (Lynch et al, 2011), chronic obstructive pulmonary disease (Marc et al, 2004;Zhang et al, 2011), cryptogenic and large-vessel disease subtypes of stroke (Stokowska et al, 2011), heart failure (Gombos et al, 2012), cerebral arteriovenous malformations (Haque et al, 2011), asthma (Joks et al, 2008), gestational diabetes mellitus (Lappas, 2011), SLE (Wild et al, 1990), acute relapses in multiple sclerosis (Ingram et al, 2010), IgA nephropathy/Henoch-Schonlein nephritis (Abou-Ragheb et al, 1992) and impaired renal function (Abou-Ragheb et al, 1991), atopic dermatitis (Sergeev Iu et al, 1989), psoriasis (Takematsu et al, 1986) and psoriatic arthritis (Muto et al, 1991), idiopathic pulmonary arterial hypertension (Abdul-Salam et al, 2006), postexercise malaise in myalgic encephalomyelitis/chronic fatigue syndrome (Nijs et al, 2010), AIDS-associated retinitis , and grafted corneas . In addition, C4a and C5a levels decrease after liver resection whereas C3a levels increase (Strey et al, 2009); and C3a and C4a are elevated in liver transplant recipients (Pfeifer et al, 2000).…”
Section: A Complement Peptides Are Important Biomarkers Of Diseasementioning
confidence: 99%
“…The merit of the study by Stokowska et al [7] comes from the important observation that distinct stroke etiologies may also result in distinct activation patterns of the complement system. As complement is closely involved in the activation of the immune system, these differences may result in distinct activation patterns of the immune system depending on the stroke etiology.…”
Section: Commentmentioning
confidence: 99%
“…In this issue of Cerebrovascular Diseases, Stokowska et al [7] report differences in complement activation in large-vessel disease (LVD) stroke and cryptogenic stroke.…”
Section: Commentmentioning
confidence: 99%